1996
DOI: 10.1007/bf02285159
|View full text |Cite
|
Sign up to set email alerts
|

Dextran sulfate sodium (DSS) induced experimental colitis in immunodeficient mice: Effects in CD4+-cell depleted, athymic and NK-cell depleted SCID mice

Abstract: Administration of dextran sulfate to mice, given in the drinking water results in acute or subacute colonic inflammation, depending on the administration protocol. This colonic inflammation exhibits ulceration, healing and repair, and a therapeutic response that makes it valuable for the study of mechanisms that could act in the pathogenesis of human ulcerative colitis, a disease thought to have an immunologically dependent pathogenesis. To investigate if immunological mechanisms were involved in the induction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
118
0
1

Year Published

2002
2002
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 155 publications
(129 citation statements)
references
References 43 publications
(33 reference statements)
10
118
0
1
Order By: Relevance
“…Inflammation was also clearly evident by day 5 of DSS treatment. This finding is in agreement with previous observations that inflammation in the DSSinduced colitis model systems is a rather late event that follows histological evidence of tissue damage (24,25).…”
Section: Characterization Of Dss-induced Colitis In C57bl͞6supporting
confidence: 93%
“…Inflammation was also clearly evident by day 5 of DSS treatment. This finding is in agreement with previous observations that inflammation in the DSSinduced colitis model systems is a rather late event that follows histological evidence of tissue damage (24,25).…”
Section: Characterization Of Dss-induced Colitis In C57bl͞6supporting
confidence: 93%
“…25 Many of the previous CD98 functional studies have used anti-CD98 antibodies as agonists, an approach that has proven useful for the study of signaling in a great many. 26 Indeed, our group has shown that CD98 is involved in signal recognition and transduction in Caco2-BBE cells, 9,12 these signaling events may be mediated through b1 integrins/Ca 2 þ , as CD98 is known to interact with integrins such as b1 integrins and ICAM-1. 12 In the present study, we demonstrate that the CD98 glycoprotein is expressed in Caco2-BBE monolayers, in the human intestine, and in the mouse small and large intestinal mucosa, and sought to better define the function of CD98 in these tissues.…”
Section: Discussionmentioning
confidence: 98%
“…The first cells to infiltrate the mucosa and submucosa after DSS challenge are large numbers of neutrophils and macrophages, followed by T and B lymphocytes [19]. The exact role of T and B cells in the DSS colitis model is still not known as various lymphocyte-deficient animals, such as CD4-depleted mice, nude mice and SCID mice, develop similar or aggravated colitis compared with wildtype mice [20,21] manifested as a higher mortality rate after prolonged exposure to DSS. Our data indicate that T cells are affected early in DSS-induced colitis, i.e.…”
Section: Discussionmentioning
confidence: 99%